(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The novel attempt in this study discussed the factors influencing parents and teachers in helping sluggish students. It highlights the importance of effective communication, individualized support, positive reinforcement, realistic goal-setting, consistency, differentiated instruction, emotional support, collaboration, identifying and addressing underlying issues, and patience in supporting sluggish students. The research emphasized the significance of parents and teachers working together to create a supportive environment fostering sluggish students’ growth and development. A questionnaire consisting of 280 parents and guardians employed Smart-PLS to validate the outcomes empirically. It is inferred that by considering these factors and maintaining a collaborative approach, parents and teachers can significantly impactsluggish students’ academic progress and overall well-being.